2014
DOI: 10.1038/nature13279
|View full text |Cite
|
Sign up to set email alerts
|

Focused specificity of intestinal TH17 cells towards commensal bacterial antigens

Abstract: T-helper-17 (Th17) cells have critical roles in mucosal defense and in autoimmune disease pathogenesis 1-3. They are most abundant in the small intestine lamina propria (SILP), where their presence requires colonization of mice with microbiota 4-7. Segmented Filamentous Bacteria (SFB) are sufficient to induce Th17 cells and to promote Th17-dependent autoimmune disease in animal models 8-14. However, the specificity of Th17 cells, the mechanism of their induction by distinct bacteria, and the means by which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
445
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 449 publications
(465 citation statements)
references
References 35 publications
15
445
2
3
Order By: Relevance
“…Moreover, Th17 cells in SPF mice gavaged with B. adolescentis did not display preferential Vβ14 T-cell receptor (TCR) chain use as exhibited by SFB-specific Th17 cells (Fig. 3D) (35), suggesting that the gut Th17 cells elicited by B. adolescentis and SFB were not recognizing a common immunodominant microbial antigen. Collectively, the data indicate that intestinal Th17 cells induced by B. adolescentis were symbiont-specific.…”
Section: B Adolescentis Does Not Provoke Either Intestinal or Systemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Th17 cells in SPF mice gavaged with B. adolescentis did not display preferential Vβ14 T-cell receptor (TCR) chain use as exhibited by SFB-specific Th17 cells (Fig. 3D) (35), suggesting that the gut Th17 cells elicited by B. adolescentis and SFB were not recognizing a common immunodominant microbial antigen. Collectively, the data indicate that intestinal Th17 cells induced by B. adolescentis were symbiont-specific.…”
Section: B Adolescentis Does Not Provoke Either Intestinal or Systemicmentioning
confidence: 99%
“…Therefore, B. adolescentis seems to be a bona fide intestinal symbiont akin to SFB in mice, capable of peaceful coexistence in the gut of a healthy host, despite its profound impact on the Th17 compartment. Recent studies have shown that gut Th17 cells in SFB-bearing hosts are specific for SFB-derived antigens (34,35). To determine if B. adolescentis-induced intestinal Th17 cells are analogously specific for B. adolescentis, we isolated CD4 + T cells from the small intestine of monocolonized mice and measured their cytokine responses to stimulation by lysates from various bacterial species.…”
Section: B Adolescentis Does Not Provoke Either Intestinal or Systemicmentioning
confidence: 99%
“…Whether 17 cells di erentiated in the intestine do also contribute to asthma exacerbation in the lung is not known. However, a recent report shows that 17 cells from SFB-positive mice contain a T cell receptor repertoire that is essentially speci c to SFB-derived peptides [26]. is nding does not support the possibility that 17 cells primed in the gut in response to SFB colonization exacerbate immune reactions to allergens elsewhere.…”
Section: Link Between Tregs and Microbiotamentioning
confidence: 45%
“…Elle induit la production d'IgA et l'activation d'un éventail complet des réponses T, aussi bien pro-inflammatoires que régulatrices [18,22,23]. La colonisation par SFB est en particulier indispensable pour reproduire la stimulation de la réponse TH17 induite par un microbiote complexe [22,23,32]. De façon intéressante, les effets de la SFB sur la maturation des réponses immunes intestinales murines s'accompagnent d'un effet de barrière vis-à-vis de la colonisation par des bactéries pathogènes, non seulement dans l'intestin [30] mais aussi dans les poumons [33].…”
Section: Synthèse Revuesunclassified